Integrative Effect of Reduced Tillage and Shading Enhanced Yield and Grain Quality of Fragrant Rice - Sicheng Deng; Yizhu Wu; Wentao Yi; Qichang Gu; Xiangru Tang (Agronomy, 2023)
The major challenge in fragrant rice production is to improve both yield and grain quality in fragrant rice. Reducing tillage has been singled out as an effective impact to improve grain yield. However, information on the improvement of grain yield and grain quality and their relationship is sparse. This study aimed to assess the influence of different tillage methods on rice growth during the booting stage under shading conditions. The experiments were conducted with rotary tillage and no-shading (RTNS), rotary tillage and shading (RTS), reduced tillage and no-shading (LTNS), reduced tillage and shading (LTS), no-tillage and no-shading (NTNS) and no-tillage and shading (NTS), using two fragrant rice varieties, Meixiangzhan 2 (MXZ2) and Xiangyaxiangzhan (XYXZ). Grain yield, grain quality, Malondialdehyde (MDA) content and antioxidant activities were all investigated. Our results showed that grain yield of reduced tillage and no-tillage were 27.9% and 27.0% higher than rotary tillage, respectively. In addition, with shading applied, grain yield significantly decreased. Moreover, with the application of a shading treatment, the brown rice rate, chalkiness degree and chalk grain rate decreased, while the milled rice rate, amylose content and protein content increased. The results of this study revealed that shading improves the grain quality of fragrant rice but has a negative impact on its yield while reducing tillage effectively makes up for the yield loss resulting from shading and improves rice quality.